2006
DOI: 10.1534/genetics.105.054007
|View full text |Cite
|
Sign up to set email alerts
|

The Dunce cAMP Phosphodiesterase PDE-4 Negatively Regulates Gαs-Dependent and Gαs-Independent cAMP Pools in the Caenorhabditis elegans Synaptic Signaling Network

Abstract: Forward genetic screens for mutations that rescue the paralysis of ric-8 (Synembryn) reduction-of-function mutations frequently reveal mutations that cause hyperactivation of one or more components of the Ga s pathway. Here, we report that one of these mutations strongly reduces the function of the Dunce cAMP phosphodiesterase PDE-4 by disrupting a conserved active site residue. Loss of function and neural overexpression of PDE-4 have profound and opposite effects on locomotion rate, but drug-response assays s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 60 publications
4
62
0
Order By: Relevance
“…By RNAi and/or mutant analyses of the six PDE homologs in C. elegans (Charlie et al 2006), we found that the pde-2 gene is required for normal body size regulation (Figure 9 and data not shown). pde-2 encodes the closest C. elegans homolog of human cGMPdependent 39,59-cyclic phosphodiesterase 2A (PDE2A).…”
Section: Role Of the Extracellular Domain Of Gcy-12mentioning
confidence: 94%
“…By RNAi and/or mutant analyses of the six PDE homologs in C. elegans (Charlie et al 2006), we found that the pde-2 gene is required for normal body size regulation (Figure 9 and data not shown). pde-2 encodes the closest C. elegans homolog of human cGMPdependent 39,59-cyclic phosphodiesterase 2A (PDE2A).…”
Section: Role Of the Extracellular Domain Of Gcy-12mentioning
confidence: 94%
“…The antibody was affinity purified using purified GST-UNC-29 fusion protein coupled to Aminolink Plus (Pierce) after presorbing 10 ml of serum to 10 mg of pure GST to remove GST-specific antibodies. GST and GST-UNC-29 fusions were produced using methods similar to those previously described (Charlie et al 2006b). To confirm the specificity of the UNC-29 antibody, we tested it on unc-29(x29) null mutants.…”
Section: Methodsmentioning
confidence: 99%
“…The density of synapses in the sublateral processes is low (Charlie et al 2006b), thus permitting resolution of what are likely to be individual DCVs.…”
Section: Figure S2mentioning
confidence: 99%
“…We prepared freeze-cracked 4% paraformaldehyde fixed worms for immunostaining as described (Charlie et al 2006a;Charlie et al 2006b), with the exception that we fixed worms for anti-FMRFamide staining for 16 h at 6° C . For immunostaining of FMRFamide neuropeptides, we co-immunostained N2 and unc-43(ce685) fixed animals using Rabbit antiFMRFamide antiserum (1/2000) and Goat anti-UNC-47 antiserum (1/12,000) ), using Donkey anti-Rabbit Dylight 550 and Donkey anti-Goat Dylight 488 secondary antibodies (Pierce).…”
Section: Immunostainingmentioning
confidence: 99%
See 1 more Smart Citation